A surface-chimeric metal-catalyzed PAN-based carbon fiber electrode, a preparation method thereof and application thereof in a flow battery
Patent Information
- Application Number
- CN202611257844.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明旨在解决现有碳纤维液流电池电极表面惰性、催化活性弱,传统金属改性电极负载浅、结合力差、金属颗粒易溶蚀脱落、稳定性不足的技术难题
[0020]本发明突破传统表层负载改性思路,依托PAN原丝原位浸渍+两步梯度热处理物相调控核心技术,形成独有嵌合包覆结构,具备以下核心创新与技术优势,具体如下:
Smart Images

Figure CN122992099A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of energy storage battery electrode material technology, specifically relating to a PAN-based carbon fiber electrode with surface-intercalated metal catalyst, its preparation method, and its application in flow batteries, specifically in all-vanadium and iron-chromium flow batteries. Background Technology
[0002] Flow batteries are a core technology in the field of large-scale energy storage. With their advantages of safety, reliability, ultra-long lifespan, and independent power capacity design, they are widely used in scenarios such as renewable energy consumption and grid peak shaving. Carbon fiber electrodes, as a core component of flow batteries, directly determine the battery's reaction kinetics, the degree of side reactions, and cycle life through their surface structure, catalytic activity, and stability.
[0003] Existing commercially available PAN-based carbon fiber electrodes primarily use graphite felt as the matrix, undergoing post-treatment activation processes such as heat treatment, acid treatment, and surface catalyst loading to enhance the surface reactivity and selectivity of the electrode material. However, current mainstream metal catalytic modification technologies mostly employ surface loading methods such as post-impregnation, spraying, and electrodeposition, which have fundamental technical drawbacks: the metal catalyst is only physically attached to the carbon fiber surface, resulting in poor adhesion and easy detachment under long-term charge-discharge cycles and acidic electrolyte immersion environments; furthermore, exposed metal particles are in direct contact with the electrolyte, exhibiting poor chemical and electrochemical stability, and their catalytic activity rapidly declines under long-term service, failing to meet the long-cycle, high-stability application requirements of flow batteries. In addition, post-treatment processes are complex and energy-intensive, hindering large-scale production.
[0004] Furthermore, traditional modification processes cannot achieve deep coupling between metal catalysts and carbon matrices, making it difficult to simultaneously achieve high catalytic activity and long-term stability. Moreover, the preparation processes are complex and energy-intensive, significantly limiting the industrialization of high-performance flow batteries. Therefore, developing a high-performance carbon fiber electrode preparation technology that achieves deep metal catalyst integration, carbon layer protection, uniform dispersion, and long-term stability is of great significance in addressing these industry bottlenecks. Summary of the Invention
[0005] This invention aims to address the technical challenges of existing carbon fiber flow battery electrodes, such as surface inertness, weak catalytic activity, shallow loading, poor bonding, easy dissolution and detachment of metal particles, and insufficient stability. It provides a method for preparing a chimeric metal-catalyzed carbon fiber electrode based on in-situ modification of PAN precursor fibers and a two-step gradient thermal treatment. Through pre-oxidation-carbonization dual-stage phase regulation, the method achieves a gradient evolution of the metal catalyst from surface adsorption → oxide chimerism → carbon coating of metal nanoparticles, resulting in a highly active, highly stable, multi-level porous integrated carbon fiber electrode that significantly improves the reaction kinetics and cycle stability of flow batteries.
[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: a PAN-based carbon fiber electrode with surface-embedded metal catalyst prepared by the above method, wherein the electrode uses PAN-based carbon fiber as the matrix, and the metal catalyst nanoparticles are not attached to the fiber surface, but are embedded in the carbon fiber surface skeleton, and the surface of the metal particles is in situ coated with a dense nano-carbon protective layer; the electrode as a whole has a multi-level porous structure and has excellent conductivity, catalytic activity and electrochemical stability.
[0007] A method for preparing a PAN-based carbon fiber electrode with a surface-intercalated metal catalyst includes the following steps:
[0008] 1) Preparation of precursor solution: Dissolve the metal-based catalyst precursor in deionized water and stir thoroughly to obtain a uniform and transparent aqueous solution of the metal precursor.
[0009] 2) In-situ impregnation modification of fibers: PAN fiber filaments are selected and immersed in the above-mentioned aqueous solution of metal precursor. The surface is treated at a constant temperature for 10-60 min to allow metal ions to be uniformly adsorbed, penetrated and anchored in the surface structure of PAN fibers. After removal and drying, metal ion modified pretreated PAN fibers are obtained.
[0010] 3) Gradient heat treatment molding: The pretreated PAN fibers are subjected to segmented gradient pre-oxidation treatment and high-temperature carbonization treatment in sequence. Through two-step gradient phase transformation, a PAN-based carbon fiber electrode with surface-embedded metal catalyst and surface-coated nano carbon layer and multi-level pore structure is finally obtained.
[0011] Furthermore, in step 1), the metal-based catalyst precursor includes one or more of BiCl3, SbCl3, SnCl4, NbCl4, and In(NO3)3, and the mass percentage concentration of the metal precursor in the aqueous solution is 0.5-5%.
[0012] Furthermore, in step 2), the PAN fiber precursor has a single filament diameter of 8~27 μm, a smooth surface, and a dense structure, providing a stable matrix for uniform intercalation and loading of metal ions; the impregnation treatment temperature is 20~60 ℃.
[0013] Furthermore, in step 3), the segmented gradient pre-oxidation process conditions are as follows: under an air atmosphere, a gradient heating method is used to perform segmented constant temperature heat treatment for 12 to 30 hours in the range of 220 ℃ to 320 ℃; the pre-oxidation stage realizes the cyclization and cross-linking curing of PAN fibers, and at the same time, the metal salt precursors adsorbed on the surface are fully oxidized and transformed into metal oxides, which are in situ embedded and fixed inside the fiber surface skeleton.
[0014] Furthermore, in step 3), the segmented gradient pre-oxidation process conditions are as follows: under an air atmosphere, using a gradient heating method, slowly oxidize at 220-260℃ for 5-10 hours, and then slowly oxidize at 280-300℃ for 10 hours.
[0015] Furthermore, in step 3), the process conditions for the high-temperature carbonization treatment are: under the protection of nitrogen or an inert atmosphere, constant temperature heat treatment at 900 ℃~1600 ℃ for 2~5 h; the carbonization stage realizes the in-situ reduction of metal oxides into highly active metal nanoparticles, while completing the graphitization of carbon fibers, surface etching and pore formation, and in-situ generation of nano carbon layer-coated interlocking metal particles.
[0016] Furthermore, in step 3), the process conditions for the high-temperature carbonization treatment are: constant temperature heat treatment at 1050℃~1200℃ for 2~5 h under nitrogen or inert atmosphere protection.
[0017] This invention also protects the intercalated metal-catalyzed PAN-based carbon fiber electrode prepared by the above method, as well as the application of the electrode in vanadium redox flow batteries, iron-chromium redox flow batteries, etc.
[0018] This invention utilizes a segmented gradient pre-oxidation process to first convert a metal precursor loaded on the surface of PAN fibers into metal oxides in situ and anchor them into the fiber surface framework. Then, through high-temperature inert carbonization, the metal oxides are further reduced to highly active metal nanoparticles. Simultaneously, pores are created on the carbon fiber surface through etching, and a nano-carbon layer is generated in situ to coat the intercalated metal nanoparticles, constructing a unique composite structure with fiber surface intercalation, carbon layer protection, and multi-level interconnected pores. This structure can, to some extent, solve the problems of easy loss and poor electrochemical stability of traditional supported metal catalysts, while significantly increasing the number of active sites on the electrode surface, electrolyte wettability, and redox reaction kinetics, effectively suppressing side reactions. The process of this invention is green, simple, widely applicable, and can be mass-produced. The prepared PAN-based carbon fiber electrode is compatible with mainstream flow battery systems such as vanadium redox flow and iron-chromium redox flow, significantly improving battery power density and energy efficiency, and possessing extremely high industrial application value.
[0019] Core innovations and beneficial effects of this invention
[0020] This invention breaks through the traditional approach of surface loading modification, relying on the core technology of in-situ impregnation of PAN precursor fibers and two-step gradient heat treatment to control the phase composition, forming a unique interlocking and encapsulating structure. It possesses the following core innovations and technical advantages, as detailed below:
[0021] 1. Pre-oxidation stage: In-situ intercalation of metal oxides to achieve catalyst anchoring and fixation.
[0022] This invention uses PAN precursor fibers as the initial modification matrix. The uncarbonized PAN precursor fibers have a loose structure and abundant pores, allowing for deep and uniform penetration and adsorption of metal ions compared to finished carbon fibers, eliminating the problems of surface floating and uneven distribution. During the segmented gradient pre-oxidation process at 220~320 ℃, the PAN fibers gradually complete cyclization and cross-linking, and the fiber skeleton is initially solidified and shaped. Simultaneously, the loaded metal salt precursor slowly oxidizes and decomposes, transforming in situ into metal oxides, which are firmly embedded and anchored within the fiber surface skeleton structure, rather than merely adhering to the surface. This fundamentally prevents catalyst detachment and loss, laying the structural foundation for subsequent carbonization modification. The gradient heating process avoids catalyst agglomeration and peeling caused by rapid pyrolysis, ensuring uniform dispersion of the metal components.
[0023] 2. Carbonization stage: In-situ phase transformation + nano-carbon layer coating, maximizing stability.
[0024] During the high-temperature inert carbonization process, the metal oxides embedded in the fiber surface are reduced in situ by the carbon matrix into highly active metal nanocatalytic particles. Simultaneously, the PAN fibers undergo deep carbonization and graphitization, and the fiber surface is controllably etched, constructing a rich, multi-level micro-nano porous structure that significantly improves specific surface area and electrolyte wettability. Most importantly, a dense nano-carbon protective layer is generated in situ on the fiber surface during carbonization, completely encapsulating the internally embedded metal nanoparticles and ensuring the metal catalyst is completely removed from its exposed state. This composite protective structure of fiber embedding and carbon layer coating can completely isolate the acidic electrolyte from direct contact with the metal particles, effectively inhibiting the chemical dissolution and electrochemical oxidation failure of the metal components, thus solving the industry pain points of poor stability and rapid cycle decay of traditional metal-modified electrodes.
[0025] 3. Synergistic effect of structure, dual improvement of catalytic performance and side reaction inhibition ability.
[0026] The electrode prepared by this invention has three advantages: a hierarchical porous structure, highly dispersed intercalated metal active sites, and a highly conductive carbon matrix. The hierarchical porous structure accelerates electrolyte penetration and ion transport, reducing concentration polarization in the battery. The uniformly intercalated metal nanocatalyst has excellent redox catalytic activity, which can significantly accelerate the reaction kinetics of vanadium and iron-chromium ions, thereby increasing the battery power density. At the same time, the metal component has high hydrogen overpotential characteristics, which, combined with a stable coating structure, can effectively suppress the hydrogen evolution side reaction at the negative electrode of the flow battery, reduce electrolyte loss and interface failure, and significantly improve the battery energy efficiency and cycle life.
[0027] 4. Simple process, green and controllable, suitable for large-scale mass production
[0028] This invention uses PAN precursor yarn as the initial raw material and simultaneously achieves in-situ impregnation modification with aqueous solution and two-step gradient heat treatment during the carbon fiber material preparation process. It eliminates the need for complex post-processing procedures, has controllable process parameters, low cost, and wide applicability. It can be adapted to large-scale industrial continuous production and has significant industrialization advantages. Attached Figure Description
[0029] Figure 1 Scanning electron microscope images of the pure PAN-based carbon fiber electrode (a) prepared for Comparative Example 2, the Bi metal-intercalated carbon-coated PAN-based carbon fiber electrode (b) prepared for Example 1, and the Sb metal-intercalated carbon-coated PAN-based carbon fiber electrode (c) prepared for Example 2.
[0030] Figure 2 Cyclic voltammetry curves (scan rate: 10 mV·s) of the Bi metal-intercalated carbon-coated PAN-based carbon fiber electrode (a) prepared in Example 1, the Sb metal-intercalated carbon-coated PAN-based carbon fiber electrode (b) prepared in Example 2, and blank PAN-based carbon nanofiber electrode material (PCF) in 0.1 M VOSO4 + 2 M H2SO4. -1 ). Detailed Implementation
[0031] The present invention will be further described in detail and completely below with reference to specific embodiments. The process parameters of all embodiments strictly match the scope of the claims and do not have any limiting effect.
[0032] Example 1
[0033] A method for preparing a PAN-based carbon fiber electrode with a surface-intercalated metal catalyst, comprising the following steps:
[0034] 1) Solution preparation: Weigh an appropriate amount of BiCl3 and dissolve it in deionized water to prepare a homogeneous precursor aqueous solution with a mass concentration of 1.5%. Stir at room temperature for 20 min until completely dissolved.
[0035] 2) Impregnation modification: PAN precursor fibers with a single filament diameter of 16 μm were selected, completely immersed in the above solution, and impregnated at a constant temperature of 40 °C for 30 min. After removal, they were dried at room temperature to obtain metal ion modified pretreated PAN fibers.
[0036] 3) Gradient heat treatment: The pretreated fibers are placed in a muffle furnace in an air atmosphere and a segmented gradient heating method is adopted. First, they are slowly oxidized at 260℃ for 6 hours, and then slowly oxidized at 280℃ for 10 hours, so that the metal salt is fully converted into metal oxide and embedded in the fiber surface. Then, they are transferred to a carbonization furnace and carbonized at 1050℃ for 2 hours in a nitrogen atmosphere. After natural cooling, they are taken out to obtain Bi-PCF, a carbon-coated PAN-based carbon fiber electrode with Bi metal intercalation.
[0037] Example 2
[0038] 1) Solution preparation: Weigh SbCl3 and dissolve it in deionized water to prepare a 2% (w / w) precursor aqueous solution;
[0039] 2) Impregnation modification: Select PAN precursor fibers with a single filament diameter of 16 μm, impregnate them in the above solution at a constant temperature of 60 °C for 15 min, and then dry them for later use;
[0040] 3) Gradient heat treatment: The pretreated fibers are placed in a muffle furnace in an air atmosphere and a segmented gradient heating method is adopted. First, they are slowly oxidized at 220℃ for 10 hours, and then slowly oxidized at 300℃ for 10 hours, so that the metal salt is fully converted into high-valence metal oxides and embedded in the fiber surface. Then, they are transferred to a carbonization furnace and carbonized at 1200℃ for 2 hours in a nitrogen atmosphere. After natural cooling, they are taken out to obtain Sb-embedded carbon-coated PAN-based carbon fiber electrode Sb-PCF.
[0041] Example 3
[0042] 1) Solution preparation: Mix SnCl4 and In(NO3)3 in a 1:1 mass ratio, dissolve in deionized water to prepare a mixed precursor solution with a total mass concentration of 3%, and stir until homogeneous;
[0043] 2) Impregnation modification: PAN precursor fibers with a single filament diameter of 27 μm were selected and impregnated in the above solution at a constant temperature of 30 °C for 40 min, followed by drying pretreatment;
[0044] 3) Gradient heat treatment: The pretreated fibers are placed in a muffle furnace in an air atmosphere and a segmented gradient heating method is adopted. First, they are slowly oxidized at 220℃ for 5 hours, and then slowly oxidized at 290℃ for 10 hours to fully convert the metal salt into metal oxide and embed it in the fiber surface. Then, they are transferred to a carbonization furnace and carbonized at 1300℃ for 2 hours in a nitrogen atmosphere. After natural cooling, they are taken out to obtain In-Sn metal intercalated carbon-coated PAN-based carbon fiber electrode.
[0045] Comparative Example 1: Traditional post-impregnation loaded metal-modified carbon fiber electrode
[0046] Commercially available PAN-based graphite felt was selected as the matrix. A BiCl3 solution of the same concentration as in Example 1 was used for impregnation at room temperature for 45 minutes, followed by drying and carbothermic reduction treatment at 800 degrees Celsius for 1 hour. The resulting electrode exhibits sparse and uneven metal particles, physically adhering only to the surface of the carbon fiber product. It lacks fiber intercalation and in-situ carbon layer coating, representing a traditional exposed metal-modified electrode. Bi vaporizes significantly, resulting in a low loading capacity.
[0047] Comparative Example 2: Pure PAN-based carbon fiber electrode (blank group)
[0048] The original PAN precursor fiber was directly used and treated with the same pre-oxidation and carbonization process without any metal precursor impregnation modification, and was used as a blank control electrode PCF.
[0049] Example 4: Performance Testing and Comparative Analysis
[0050] 1. Surface morphology characterization:
[0051] Figure 1 Scanning electron microscope images of the blank PAN-based carbon nanofiber electrode material (PCF) prepared for Comparative Example 2 (a), the bismuth-doped PAN-based carbon nanofiber electrode material (Bi-PCF) prepared in Example 1 (b), and the antimony-doped PAN-based carbon nanofiber electrode material (Sb-PCF) prepared in Example 2 (c).
[0052] like Figure 1 As shown in (a): The blank PAN-based carbon nanofiber electrode material (PCF) prepared in Comparative Example 2 has a smooth and flat fiber surface without any load.
[0053] like Figure 1 (b) shows that the surface of the bismuth-doped PAN-based carbon nanofiber electrode material (Bi-PCF) prepared in Example 1 was simultaneously etched and loaded with Bi.
[0054] like Figure 1 As shown in (c): The surface of the antimony-doped PAN-based carbon nanofiber electrode material (Sb-PCF) prepared in Example 2 was simultaneously etched and loaded with Sb.
[0055] 2. Cyclic Voltammetry (CV) Curve Test:
[0056] Methods: The electrochemical performance of the materials was tested using a three-electrode system, with the 0.5 × 0.5 cm electrode prepared in Example 1 being used as the test electrode. 2 Bi-PCF, Sb-PCF prepared in Example 2, and blank PCF prepared in Comparative Example 2 were used as working electrodes; a 232-type saturated calomel electrode was used as the reference electrode; and a 1×1 cm⁻¹ electrode was used as the reference electrode. 2 A platinum sheet was used as the auxiliary electrode, and 0.1 M VOSO4 + 2.0 M H2SO4 was used as the electrolyte. CV testing was performed at a scan rate of 10 mV·s. -1 .
[0057] Figure 2Figures (a) and (b) show the measured cyclic voltammetry curves. The results indicate that the redox peak current densities of the Bi-PCF and Sb-PCF electrodes are significantly higher than those of the blank PCF electrode under the same potential window, and the peak shapes are more symmetrical. The polarization voltage is also significantly reduced, indicating that metal doping significantly improves the catalytic kinetics, reaction reversibility, and reaction selectivity of the electrode. This verifies the effectiveness of the preparation process of this invention in constructing highly active catalytic sites.
[0058] 3. Battery performance test
[0059] The electrodes of Example 1, Comparative Example 1, and Comparative Example 2 of this invention were immersed in 1.6 MV water. 3.5+ The loss rate of metal ions from the electrode surface was investigated by ICP testing after 500 h in an electrolyte of +3 M H2SO4. Furthermore, all-vanadium redox flow single cells were assembled using three different electrodes, with Nafion 212 as the separator and graphite as the bipolar plate, at 250 mA cm⁻¹. -2 The results of 500 charge-discharge cycles at different current densities are shown in Table 1.
[0060] Table 1
[0061]
[0062] The test data shows that in the conventional, post-loaded Comparative Example 1 electrode, the metal catalyst is exposed on the fiber surface, making it easily eroded and lost in acidic electrolytes. This results in severe performance degradation and extremely poor stability under long-term cycling. The blank pure carbon fiber electrode exhibits insufficient catalytic activity, prominent hydrogen evolution side reactions, and the worst battery performance. In contrast, this invention employs an intercalated coated electrode prepared by in-situ impregnation of the original fiber and a two-step gradient heat treatment. Through a dual protection mechanism of pre-oxidized oxide anchoring and carbonized carbon layer coating, the loss rate of metal components is significantly reduced, effectively addressing the stability shortcomings of traditional modified electrodes. Simultaneously, the uniformly intercalated highly active metal sites and multi-level porous structure synergistically enhance the effect, combining excellent catalytic kinetics and hydrogen evolution suppression capabilities. This results in a significant improvement in battery energy efficiency and cycle stability, fully verifying the innovation and advancement of this invention.
Claims
1. A PAN-based carbon fiber electrode with a surface-intercalated metal catalyst, characterized in that, Metal catalyst nanoparticles are embedded within the carbon fiber surface skeleton, and the surface of the metal catalyst nanoparticles is in situ coated with a dense nano-carbon protective layer; the electrode as a whole has a multi-level micro-nano pore structure.
2. The method for preparing a PAN-based carbon fiber electrode with a surface-intercalated metal catalyst as described in claim 1, characterized in that, Includes the following steps: 1) Preparation of precursor solution: Dissolve the metal-based catalyst precursor in deionized water and stir thoroughly to obtain a uniform and transparent aqueous solution of the metal precursor. 2) In-situ impregnation modification of fibers: PAN fiber filaments are immersed in an aqueous solution of metal precursor and subjected to constant temperature surface impregnation treatment for 10~60 min under constant temperature conditions. After removal and drying, metal ion modified pretreated PAN fibers are obtained. 3) Gradient heat treatment molding: The pretreated PAN fibers are subjected to segmented gradient pre-oxidation treatment and high-temperature carbonization treatment in sequence, and after cooling, PAN-based carbon fiber electrodes with surface-embedded metal catalysts are obtained.
3. The method for preparing a PAN-based carbon fiber electrode with a surface-intercalated metal catalyst according to claim 2, characterized in that, In step 1), the metal-based catalyst precursor includes one or more of BiCl3, SbCl3, SnCl4, NbCl4, and In(NO3)3, and the mass percentage concentration of the metal catalyst precursor in the aqueous solution is 0.5-5%.
4. The method for preparing a PAN-based carbon fiber electrode with a surface-intercalated metal catalyst according to claim 2, characterized in that, In step 2), the diameter of the PAN fiber precursor is 8~27 μm; the impregnation treatment temperature is 20~60℃.
5. The method for preparing a PAN-based carbon fiber electrode with a surface-intercalated metal catalyst according to claim 2, characterized in that, In step 3), the process conditions for the segmented gradient pre-oxidation treatment are as follows: under an air atmosphere, using a gradient heating method, segmented constant temperature heat treatment is performed for 12 to 30 hours within the range of 220 ℃ to 320 ℃.
6. The method for preparing a PAN-based carbon fiber electrode with a surface-intercalated metal catalyst according to claim 5, characterized in that, The process conditions for the segmented gradient pre-oxidation treatment are as follows: under an air atmosphere, slow oxidation is carried out at 220-260℃ for 5-10 hours, followed by slow oxidation at 280-300℃ for 10 hours.
7. The method for preparing a PAN-based carbon fiber electrode with a surface-intercalated metal catalyst according to claim 2, characterized in that, In step 3), the process conditions for the high-temperature carbonization treatment are: constant temperature heat treatment at 900 ℃~1600 ℃ for 2~5 h under nitrogen or inert atmosphere protection.
8. The method for preparing a PAN-based carbon fiber electrode with a surface-intercalated metal catalyst according to claim 7, characterized in that, In step 3), the process conditions for the high-temperature carbonization treatment are: constant temperature heat treatment at 1050℃~1200℃ for 2~5 h under nitrogen or inert atmosphere protection.
9. The application of a PAN-based carbon fiber electrode with a surface-intercalated metal catalyst as described in claim 1 in a flow battery.
10. The application according to claim 9, characterized in that, The flow batteries include vanadium redox flow batteries and iron-chromium redox flow batteries.